Influence of grape cultivars and technological treatments on quality of grape brandies - Milanov Goran; Beleski Klime; Cvetković Julijana; Nedelkovski Duško (Agroznanje, 2014)
The paper investigates the impact and the selection of grape varieties, as well as finding out, improvement and implementation of the most appropriate technological processes and production methods on the quality of strong alcoholic drinks from grape. We examined grape varieties such as Smederevka and Vranac that are present in Macedonia as well as table cultivar Afus Ali for brandy production. The intensities of the different types of the applied technologies in the production of three types of brandies: wine brandy, grape brandy and pomace brandy. In this context, we studied the effects of fine lees on quality of winebrandy, the impact of stem presence and time of distillation on the quality of grape and pomace brandy. Chemical and gas chromatographic analysis was performed and brandies were sensory evaluated. The effect of technological processes on the sensory characteristics was determined, as well.